Managing the Marine Environment, Conceptual Models and Assessment Considerations for the European Marine Strategy Framework Directive - Smith, Christopher J.; Papadopoulou, Konstantia-Nadia; Barnard, Steve; Mazik, Krysia; Elliott, Michael; Patrício, Joana; Solaun, Oihana; Little, Sally; Bhatia, Natasha; Borja, Angel (Frontiers in Marine Science, 2016)
Conceptual models summarize, visualize and explain actual or predicted situations and how they might be tackled. In recent years, Pressure-State-Response (P-S-R) frameworks have been central to conceptualizing marine ecosystem issues and then translating those to stakeholders, environmental managers and researchers. Society is concerned about the risks to the natural and human system posed by those Pressures (thus needing risk assessment) and then needs to act to minimize or compensate those risks (as risk management). This research relates this to the DPSIR (Drivers-Pressure-State(change)-Impact-Response) hierarchical framework using standardized terminology/definitions and lists of impacting Activities and Pressures affecting ecosystem components, incorporating the European Marine Strategy Framework Directive (MSFD) legal decision components. This uses the example of fishing activity and the pressure of abrasion from trawling on the seabed and its effects on particular ecosystem components. The mechanisms of Pressure acting on State changes are highlighted here as an additional refinement to DPSIR. The approach moves from conceptual models to actual assessments including: assessment methodologies (interactive matrices, ecosystem modeling, Bayesian Belief Networks, Bow-tie approach, some assessment tools) data availability, confidence, scaling, cumulative effects and multiple simultaneous Pressures, which more often occur in multi-use and multi-user areas. In defining and describing the DPSIR Conceptual Framework we consider its use in real-world ecosystems affected by multiple pressures or multiple mechanisms of single pressures, and show how it facilitates management and assessment issues with particular relevance to the MSFD.